HISTORICAL PORTRAIT OF SHIITES AND SUNNIS IN IRAQ IN THE POEM “NACHNU SYA'BUN LAA YASTACHII”: A LITERARY SOCIOLOGICAL PERSPECTIVE - Saddam Reza Hamidi; Dihyat Haniful Fawad (Arabic Literature Department, 2024)
The poem “Nachnu Sya’bun Laa Yastachii” by Ahmad Numaini serves as a socio-historical critique, reflecting sectarian tensions and political dynamics in Iraq. This study explores two primary aspects: first, how the poem reflects the socio-political context of Iraq during its composition, and second, its portrayal of Shiite history as interpreted by the poet. Employing a qualitative research methodology with Alan Swingewood’s literary sociology approach, this study analyzes the poem’s use of historical symbolism, particularly the Karbala tragedy, to critique patterns of betrayal and disunity within the Muslim community. The findings reveal that the poem functions as both a reflection of its era and a critique of contemporary socio-political conditions. This study highlights the role of literature in documenting and critiquing historical and societal phenomena, reinforcing its relevance as a medium for social commentary.